Altered Neuromodulatory Drive May Contribute to Exaggerated Tonic Vibration Reflexes in Chronic Hemiparetic Stroke - McPherson, Jacob G.; McPherson, Laura M.; Thompson, Christopher K.; Ellis, Michael D.; Heckman, Charles J.; Dewald, Julius P. A. (Frontiers in Human Neuroscience, 2018)
Exaggerated stretch-sensitive reflexes are a common finding in elbow flexors of the contralesional arm in chronic hemiparetic stroke, particularly when muscles are not voluntarily activated prior to stretch. Previous investigations have suggested that this exaggeration could arise either from an abnormal tonic ionotropic drive to motoneuron pools innervating the paretic limbs, which could bring additional motor units near firing threshold, or from an increased influence of descending monoaminergic neuromodulatory pathways, which could depolarize motoneurons and amplify their responses to synaptic inputs. However, previous investigations have been unable to differentiate between these explanations, leaving the source(s) of this excitability increase unclear. Here, we used tonic vibration reflexes during voluntary muscle contractions of increasing magnitude to infer the sources of spinal motor excitability in individuals with chronic hemiparetic stroke. We show that when the paretic and non-paretic elbow flexors are preactivated to the same percentage of maximum prior to vibration, tonic vibration reflexes remain significantly elevated in the paretic arm. We also show that the rate of vibration-induced torque development increases as a function of increasing preactivation in the paretic limb, even though the amplitude of vibration-induced torque remains conspicuously unchanged as preactivation increases. It is highly unlikely that these findings could be explained by a source that is either purely ionotropic or purely neuromodulatory, because matching preactivation should control for the effects of a potential ionotropic drive (and lead to comparable tonic vibration reflex responses between limbs), while a purely monoaminergic mechanism would increase reflex magnitude as a function of preactivation. Thus, our results suggest that increased excitability of motor pools innervating the paretic limb post-stroke is likely to arise from both ionotropic and neuromodulatory mechanisms.